Study about Linen Fabric on the Surface Applied Natural Herbal Dyes to Improving the Colour Fastness and Absorbency Characteristic Properties - Ramratan Guru; Rohit Kumar; Deepika Grewal (Novel Perspectives of Engineering Research Vol. 2, 2021)
These day, natural herbal textile dye garment products are preferred by all consumers. These herbal dye cloths are more environmentally friendly. It provides a non-toxic, chemical-free product that does not harm the environment or nature. Herbal textiles are dyed entirely with herbal extracts, without the use of any chemicals. Herbs are used instead of vegetable dyes because they are not only natural but also have medicinal value. These herbs are applied directly to the fabric with the help of natural ingredients, so that the medicinal value of the herbs is preserved, because synthetic dyes create a large amount of waste and unfixed colourants pose a serious health risk and disrupt the eco balance of nature. Environmental concerns about the production and use of synthetic dyes have reignited consumer interest in natural dyes. In this study, we used natural herbal dyes on the surface of linen fabrics. Turmeric, aloe vera, neem, beetroot, pomegranate, and onion were used as natural herbal dyes in this work. Color fastness and dye absorbency performance have been improved using edible gum and cow urine. We have found that herbal dyes appearances on linen fabric surface is very good. It has observed that, a dry and wet rubbing fastness property has very good herbal dyes on linen fabric surface. The primary goal of this research is to provide a new approach to natural herbal dyes products that will be more widely used in the textile industry. It will also aid in the reduction of diseases such as skin allergies and skin infections.